ECOLOGICAL THINK CONTENT DESCRIPTION (Conferencea, 2023)
In the article, while strengthening the positions of a new humanistic type of ecological culture, the problem of what direct concepts exist about the biosocial system "man-society-nature" plays a major role. First of all, it will be discussed about how it will be introduced into environmental education and upbringing, and how the foundations of the past consumer culture will be critically revised.